Islamic Higher Education as Moral Safeguarding: Religious Motivations among Coastal Communities in Indonesia - Zahra Ulfi Hanifah; Muhammad Romadlon Habibullah (Journal of Islamic Education Thought and Development, 2026)
This study aims to explore the religious motivations of coastal communities in Indonesia in choosing Islamic Higher Education Institutions (PTI) as a moral and spiritual bulwark for their children. The study used a qualitative approach with a case study design to understand the religious, social, and cultural considerations underlying coastal communities' educational choice of PTI. Data were collected through in-depth interviews, observations, and documentation involving parents, religious leaders, and coastal communities. The research findings indicate that strong religious traditions are a major factor influencing coastal families in choosing PTI. Parents view PTI not only as an academic educational institution, but also as a moral and spiritual bulwark capable of maintaining their children's faith, character, and behavior amidst the exposed coastal environment that is vulnerable to negative social influences. This educational choice is driven by three main motivations: protecting children's morality, fulfilling religious obligations in pursuing Islamic knowledge as an investment for this world and the hereafter, and preparing future da'wah cadres capable of independently meeting the spiritual needs of coastal communities. Furthermore, the community believes that the integration of religious and general knowledge at PTI can produce graduates who are intellectually competent and spiritually resilient in facing the uncertainties of fishing life. Islamic boarding schools (PTI) are also seen as a means of maintaining the family's Islamic identity, gaining blessings of sustenance, and achieving a balance between worldly success and eternal happiness. Thus, this study demonstrates that coastal communities' decisions to choose Islamic boarding schools (PTI) are not solely based on academic considerations, but also on the need for moral protection, strengthening religious identity, and sustaining Islamic values ​​in the lives of coastal communities. This research contributes to expanding the study of the sociology of Islamic education by positioning Islamic boarding schools (PTI) as a strategic institution in maintaining the moral and spiritual resilience of coastal Muslim communities in contemporary Indonesia.